Gabriele Baumann: capstone - Baumann, Gabriele, artist (Colorado State University. Libraries, 2022)
The artist's statement: "The role of the designer is that of a good, thoughtful host anticipating the needs of his guests." Through my work, I want to convey a feeling of understanding and relatability, creating designs that you could look at and feel almost nostalgic. I mainly used adobe programs but will include other forms of art to help me portray the feeling I want too. Being able to create a design that others can relate to but also following the criteria provided for me is something that I aim for in my journey.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design